The crisis of the division of powers (Società e diritti, 2017)
The author draws attention to the crisis of the principle of divisions of powers and in particular the supply of judicial power or the difficulty of judges in the face of legislation not only confused but also fragmented when introducing a variety of special rites into judgment.Key words: Ruleof Law, Judiciary, Society